Komunikasi Tematik Dalam Branding Destinasi Urban: Studi Komparatif Delta Fishing, Cafe Bintang Lima, Dan Monkasel Surabaya - Fikri Amrilllah; Stefanus Irwananda Susanto; Muhammad Rifky; Mohammad Insan Romadhan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The rapid development of urban areas has led to the emergence of tourist destinations that function not only as recreational spaces but also as tools for shaping the city’s image. To strengthen the competitiveness and identity of a destination, thematic communication becomes a crucial strategy, encompassing visual, narrative, and atmospheric elements that are integrated into the visitor experience. This article explores the implementation of thematic communication in the branding of three urban destinations in East Java: Delta Fishing, Café Bintang Lima, and the Submarine Monument (Monkasel), using a comparative study and qualitative descriptive analysis. Data were collected through field observations, visual documentation, and interviews with managers and visitors. The results show that each destination applies a different thematic communication approach: Delta Fishing emphasizes environmental education values, Café Bintang Lima conveys affordable luxury through visual and digital media, while Monkasel offers an immersive historical experience. These findings highlight that the effectiveness of thematic communication depends on the alignment of messages, media used, and the ability to build emotional connections with the audience. With the right strategy, thematic communication can enhance the image and competitiveness of tourist destinations, especially amid increasing competition in urban tourism.